The importance of the Physical Environment for Child and Adolescent Mental Health Services - Shane L Rogers; Stephen J Edwards; Paul Human; Rebecca Perera (ACHSM, 2016)
Objective: This study examined the relationships between appraisals of the physical environment with the subjective experience of consumers, and work satisfaction of clinicians, in Child and Adolescent Mental Health Services (CAMHS). Design, setting, and outcome measures: A survey of clinicians, parent/guardians, and child/adolescents was conducted across eight community CAMHS in Western Australia. Respondents evaluated the waiting room and therapy rooms on a number of environmental attributes, and factor analysis was carried out to confirm that these ratings loaded on an overall appraisal of the physical environment measure. This measure was then correlated with self-reported subjective experience of consumers, and overall work satisfaction of staff members. Results: Clinicians were found to be much more critical of the physical environment compared with consumers. Moderate associations were found between appraisal of the physical environment and subjective experience of consumers. A strong positive association was found between clinician appraisal of the physical environment and overall work satisfaction. Conclusions: The present study adds to the limited existing research arguing for the important role that the physical environment can have upon both consumer and staff experience in mental health settings. The present study provides empirical evidence to justify steps being taken to enhance the physical environment in mental health clinics. The inter-relationship between physical environment attributes suggests there is potential for managers to improve the overall perception of clinic space via relatively small actions (e.g., adding a nice piece of artwork). Abbreviations: CAMHS - Child and Adolescent Mental Health Services.